Preparation method of high-performance PEM electrolytic water membrane electrode anode catalyst layer slurry
By adding precious metal substances such as platinum black to the anode catalytic layer, the conductivity and catalytic activity are improved, and the problem of insufficient conductivity of the anode catalyst in the prior art is solved, which significantly improves the electrolytic performance of the membrane electrode.
Patent Information
- Application Number
- CN202311653625.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-05
- Publication Date
- 2024-12-13
AI Technical Summary
The conductive performance of the existing PEM electrolytic membrane electrode anode catalyst is insufficient, which affects the overall performance of the membrane electrode.
The anode catalytic layer adds precious metal substances with excellent conductivity and catalytic oxygen evolution reaction ability, such as platinum black, iridium black, ruthenium black, palladium black and cobalt black, which are uniformly dispersed on the proton exchange membrane through multi-stage dispersion technology to improve Conductivity and catalytic activity of the catalytic layer.
It effectively improves the conductivity and catalytic performance of the anode catalytic layer, improves the electrolytic performance of the membrane electrode, and avoids the problem of covering the original catalyst active sites.
Smart Images

Figure CN119121287A_ABST
Abstract
Description
Technical Field
[0002] The invention belongs to the field of fuel cell catalysts and relates to the preparation of an electrode anode catalyst slurry, and specifically to a method for preparing a high-performance PEM water electrolysis membrane electrode anode catalyst layer slurry. Background Art
[0004] In order to cope with global climate change, reduce carbon dioxide emissions and even achieve carbon neutrality, countries around the world are actively promoting the development of renewable clean energy. Hydrogen energy is considered the best energy carrier because of its clean, efficient, pollution-free, wide application, zero carbon dioxide emissions, and ability to be stored and transported. At present, the most practical and cleanest way to convert renewable clean energy into hydrogen energy is to electrolyze water. Among them, the proton exchange membrane water electrolysis device is currently the development focus of countries around the world. In the proton exchange membrane water electrolysis device, the membrane electrode assembly is the core component of the water electrolysis device, which is mainly composed of a proton membrane located in the middle, a cation and cation catalyst layer located on both sides of the proton membrane in close contact with the proton membrane, and a gas diffusion layer located outside the catalyst layer. The catalyst layer on one side of the proton exchange membrane is the anode catalyst, and the one on the other side is the cathode catalyst.
[0005] When the water electrolysis device is working, water produces and releases oxygen under the catalysis of the anode catalyst. The mechanical reaction of this process is slow, so a precious metal catalyst is needed to speed up the reaction. The commonly used precious metal catalyst is iridium oxide. At present, the anode catalyst slurry of the PEM electrolysis membrane electrode is mainly composed of catalyst, ion polymer, ultrapure water, and liquid alcohol. The main components of the catalyst are one or more of iridium oxide, ruthenium oxide, and iridium ruthenium binary oxide. The catalyst component is a metal oxide, and it will not be loaded on a conductive carrier for use, so its conductivity is poor. If it is used alone as the catalyst component of the anode catalyst layer, the electronic conduction ability of the anode catalyst layer will be weak, which will affect the overall performance of the membrane electrode.
[0006] The prior art generally uses metal oxides alone as catalyst components. The catalytic layer is the site of chemical reactions. The reaction that occurs in the anode catalytic layer is that water loses electrons and releases oxygen. In addition to being the site of chemical reactions, the catalytic layer also plays the role of conducting electrons, and the component that conducts electrons in the catalytic layer is mainly the catalyst. However, the main component of the catalyst in the anode catalytic layer of PEM water electrolysis is metal oxide - one or more of iridium oxide, ruthenium oxide, and iridium ruthenium binary oxide. The conductivity of metal oxides is not good, so the conductivity of the catalytic layer using iridium oxide alone is also not good, which ultimately affects the performance of the membrane electrode. To solve this problem, the present invention will add a substance with good conductivity and a certain ability to catalyze oxygen evolution reactions to the catalytic layer to improve the conductivity of the catalytic layer and the catalytic performance at the same time, thereby improving the water electrolysis performance of the membrane electrode. Summary of the invention
[0007] The present invention improves the conductivity of the anode catalyst layer by adding a conductive substance into the anode catalyst slurry, thereby improving the water electrolysis performance of the membrane electrode.
[0008] In order to solve the problem of poor conductivity of metal oxide catalysts in the anode catalyst layer, the present invention will improve the conductivity of the anode catalyst layer and thus improve the performance of the PEM water electrolysis membrane electrode by adding conductive substances to the anode catalyst layer. Adding conductive materials to the catalyst layer can effectively improve the conductivity of the catalyst layer, but adding materials with only conductive properties may cover the active sites of the catalyst in the original catalyst layer, resulting in a decrease in the catalytic performance of the catalyst layer and a deterioration in the performance of the membrane electrode. Therefore, the conductive substances added to the catalyst layer are not arbitrarily selected. The use of metal substances and the corresponding amount of substance added in the present invention can effectively avoid the above problems, which is a key point of the present invention.
[0009] A method for preparing an anode catalyst layer of a membrane electrode with high performance, wherein the anode catalyst layer slurry includes a metal oxide catalyst, a metal substance with excellent electrical conductivity, liquid alcohol, an ion polymer, and ultrapure water, and after multi-stage dispersion, the anode catalyst layer slurry is obtained; in the present invention, a precious metal substance with good electrical conductivity and certain catalytic activity for oxygen evolution reaction is selected and added to the anode catalyst layer, including one or more of platinum black, iridium black, ruthenium black, palladium black and cobalt black. Using precious metal substances as additives can not only effectively improve the electrical conductivity of the anode catalyst layer, but also provide a certain catalytic reaction effect, further improving the electrolysis performance of the membrane electrode.
[0010] The specific method for preparing the anode catalyst slurry is as follows: the anode catalyst iridium oxide, conductive material, ultrapure water, and liquid alcohol are added and mixed in a certain proportion, and then multi-stage dispersion is performed to finally obtain a stable anode catalyst slurry. The anode catalyst layer slurry is evenly dispersed on the proton exchange membrane by spraying or coating to obtain a high-performance electrolytic water anode catalyst layer.
[0011] Preferably, the metal oxide catalyst includes one or more of iridium oxide, ruthenium oxide, and iridium-ruthenium binary oxide.
[0012] Preferably, the conductive material is one or more of platinum black, iridium black, ruthenium black, palladium black and cobalt black.
[0013] Preferably, the liquid alcohol comprises a mixture of one or more of ethanol, n-propanol, isopropanol, n-butanol, ethylene glycol, ethoxyethanol, and methoxyethanol.
[0014] Preferably, the mass ratio of the metal oxide to the conductive material is 9:1-1:1.
[0015] Preferably, the volume ratio of the ultrapure water to the liquid alcohol is 9:1-1:9.
[0016] Preferably, the noble metal loading of the metal oxide catalyst in the anode catalyst layer slurry is 0.01-3 mg / cm 2 .
[0017] Preferably, the multi-stage dispersion includes: one or more of ball milling dispersion, ultrasonic dispersion and high shear dispersion.
[0018] Preferably, the spraying or coating means includes one or more of electrostatic spraying, ultrasonic spraying, blade coating, roller coating and slit coating.
[0019] Compared with the prior art, the advantages of the present invention are: The present invention adds one or more of platinum black, iridium black, ruthenium black, palladium black and cobalt black. These substances have excellent electrical conductivity. When added to the anode catalyst layer, the electrical conductivity of the anode catalyst layer can be effectively improved. At the same time, the addition amount provided in the present invention is also a key point, which can effectively avoid problems such as covering the active sites of the catalyst in the original catalyst layer. In addition, the added substance has a certain ability to catalyze the oxygen evolution reaction. After being added to the anode catalyst layer, it can also effectively improve the performance of the catalyst layer, thereby improving the performance of the electrolytic water membrane electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The performance diagram of the membrane electrode without adding conductive material to the anode catalyst layer at different temperatures in Example 1; Figure 2 The membrane electrode performance diagram is shown in Example 2 at different temperatures when a conductive material (platinum black) is added to the anode catalyst layer.
[0021] Figure 3 The membrane electrode performance diagram is shown in Example 3 at different temperatures when a conductive material (platinum black) is added to the anode catalyst layer.
[0022] Figure 4 The membrane electrode performance diagram is shown in Example 4 at different temperatures when a conductive material (platinum black) is added to the anode catalyst layer.
[0023] Figure 5 The membrane electrode performance diagram is shown in Example 5 at different temperatures when a conductive material (platinum black) is added to the anode catalyst layer.
[0024] Figure 6 The membrane electrode performance diagram is shown in Example 6 at different temperatures when a conductive material (platinum black) is added to the anode catalyst layer.
[0025] Figure 7The membrane electrode performance diagram is shown in Example 7 at different temperatures when a conductive material (platinum black) is added to the anode catalyst layer.
[0026] Figure 8 The membrane electrode performance diagram is shown in Example 8 at different temperatures when a conductive material (platinum black) is added to the anode catalyst layer. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with the accompanying drawings and specific examples of the specification. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0028] Example 1 The metal oxide catalyst is loaded at the anode catalyst layer at 1 mg / cm 2 The standard dosage is 50 cm2. 2 . In this embodiment, iridium oxide is used as the catalyst material, and 50 mg of iridium oxide is weighed. Ultrapure water and n-propanol are used as dispersion solvents in a ratio of 5:5, and 3 ml of each is added. Then, Nafion solution is added, and the added amount satisfies: the ratio of the mass of the metal substance to the mass of the metal oxide to the mass of Nafion is 8:2. After the above-mentioned catalyst is mixed with the dispersion solvent, ultrasonic dispersion is used to disperse the slurry. The ultrasonic dispersion time is 30 minutes. After the dispersion is completed, the slurry is evenly sprayed on the proton exchange membrane by ultrasonic spraying, and then the obtained membrane electrode is assembled to the electrolyzer for testing. The test results are as follows. Figure 1 .
[0029] Example 2 The metal oxide catalyst is loaded at the anode catalyst layer at 1 mg / cm 2 The standard dosage is 50 cm2. 2 . This embodiment uses iridium oxide as the catalyst substance and platinum black as the added conductive substance in a ratio of 8:2. Weigh 50 mg of iridium oxide and 12.5 mg of platinum black and mix them. Ultrapure water and n-propanol are used as dispersion solvents in a ratio of 5:5. Add 3 ml of each, and then add Nafion solution. The added amount satisfies: the ratio of the mass of the metal substance to the mass of the metal oxide to the mass of Nafion is 7:3. After the above-mentioned catalyst, conductive substance and dispersion solvent are mixed, ultrasonic dispersion is used to disperse the slurry. The ultrasonic dispersion time is 30 minutes. After the dispersion is completed, the slurry is evenly sprayed on the proton exchange membrane by ultrasonic spraying, and then the obtained membrane electrode is assembled to the electrolyzer for testing. The test results are as follows Figure 2 .
[0030] Example 3 The metal oxide catalyst is loaded at the anode catalyst layer at 1 mg / cm 2 The standard dosage is 50 cm2. 2 . This embodiment uses iridium oxide as the catalyst substance and ruthenium black as the added conductive substance in a ratio of 7:3. Weigh 50 mg of iridium oxide and 21.4 mg of platinum black and mix them. Ultrapure water and isopropanol are used as dispersion solvents in a ratio of 5:5. Add 3 ml of each, and then add Nafion solution. The added amount satisfies: the ratio of the mass of the metal substance to the mass of the metal oxide to the mass of Nafion is 9:1. After the above-mentioned catalyst, conductive substance and dispersion solvent are mixed, ultrasonic dispersion is used to disperse the slurry. The ultrasonic dispersion time is 30 minutes. After the dispersion is completed, the slurry is evenly sprayed on the proton exchange membrane by ultrasonic spraying, and then the obtained membrane electrode is assembled to the electrolyzer for testing. The test results are as follows Figure 3 .
[0031] Example 4 The metal oxide catalyst is loaded at the anode catalyst layer at 1 mg / cm 2 The standard dosage is 50 cm2. 2 . This embodiment uses iridium oxide as the catalyst substance and ruthenium black as the added conductive substance in a ratio of 5:5. Weigh 50 mg of iridium oxide and 50 mg of palladium black and mix them. Ultrapure water and isopropanol are used as dispersion solvents in a ratio of 5:5. Add 5 ml of each, and then add Nafion solution. The added amount satisfies: the ratio of the mass of the metal substance to the mass of the metal oxide and the mass of Nafion is 8:2. After the above-mentioned catalyst, conductive substance and dispersion solvent are mixed, ultrasonic dispersion and ball milling dispersion are used to disperse the slurry. The ultrasonic dispersion time is 30 minutes, and the ball milling dispersion time is 60 minutes. After the dispersion is completed, the slurry is evenly sprayed on the proton exchange membrane by ultrasonic spraying, and then the obtained membrane electrode is assembled to the electrolyzer for testing. The test results are as follows Figure 4 .
[0032] Example 5 The metal oxide catalyst is loaded at the anode catalyst layer at 1 mg / cm 2 The standard dosage is 50 cm2. 2. This embodiment uses iridium oxide as the catalyst substance, and platinum black and ruthenium black as added conductive substances in a ratio of 7:2:1. Weigh 50 mg of iridium oxide, 14.3 mg of platinum black, and 7.1 mg of ruthenium black, and mix them. Ultrapure water and isopropanol are used as dispersion solvents in a ratio of 5:5. Add 3 ml of each, and then add Nafion solution. The added amount satisfies: the ratio of the mass of the metal substance to the mass of the metal oxide to the mass of Nafion is 7:3. After the above-mentioned catalyst, conductive substance and dispersion solvent are mixed, ultrasonic dispersion is used to disperse the slurry. The ultrasonic dispersion time is 30 minutes. After the dispersion is completed, the slurry is evenly sprayed on the proton exchange membrane by ultrasonic spraying, and then the obtained membrane electrode is assembled to the electrolyzer for testing. The test results are as follows Figure 5 .
[0033] Example 6 The metal oxide catalyst is loaded at the anode catalyst layer at 1 mg / cm 2 The standard dosage is 50 cm2. 2 . This embodiment uses iridium oxide as the catalyst substance, and platinum black and palladium black as added conductive substances in a ratio of 7:2:1. Weigh 50 mg of iridium oxide, 14.3 mg of platinum black, and 7.1 mg of palladium black, and mix them. Ultrapure water and isopropanol are used as dispersion solvents in a ratio of 5:5. Add 3 ml of each, and then add Nafion solution. The added amount satisfies: the ratio of the mass of the metal substance to the mass of the metal oxide to the mass of Nafion is 8:2. After the above-mentioned catalyst, conductive substance and dispersion solvent are mixed, ultrasonic dispersion is used to disperse the slurry. The ultrasonic dispersion time is 30 minutes. After the dispersion is completed, the slurry is evenly sprayed on the proton exchange membrane by ultrasonic spraying, and then the obtained membrane electrode is assembled to the electrolyzer for testing. The test results are as follows Figure 6 .
[0034] Example 7 The metal oxide catalyst is loaded at the anode catalyst layer at 1 mg / cm 2 The standard dosage is 50 cm2. 2. This embodiment uses iridium oxide as the catalyst substance, and platinum black and palladium black as added conductive substances in a ratio of 7:2:1. Weigh 50 mg of iridium oxide, 14.3 mg of ruthenium black, and 7.1 mg of palladium black, and mix them. Ultrapure water and isopropanol are used as dispersion solvents in a ratio of 5:5. Add 3 ml of each, and then add Nafion solution. The added amount satisfies: the ratio of the mass of the metal substance to the mass of the metal oxide to the mass of Nafion is 9:1. After the above-mentioned catalyst, conductive substance and dispersion solvent are mixed, ultrasonic dispersion is used to disperse the slurry. The ultrasonic dispersion time is 30 minutes. After the dispersion is completed, the slurry is evenly sprayed on the proton exchange membrane by ultrasonic spraying, and then the obtained membrane electrode is assembled to the electrolyzer for testing. The test results are as follows Figure 7 .
[0035] Example 8 The metal oxide catalyst is loaded at the anode catalyst layer at 1 mg / cm 2 The standard dosage is 50 cm2. 2 . This embodiment uses iridium oxide as the catalyst substance and cobalt black as the added conductive substance in a ratio of 8:2. Weigh 50 mg of iridium oxide and 12.5 mg of cobalt black and mix them. Ultrapure water and isopropanol are used as dispersion solvents in a ratio of 5:5. Add 3 ml of each, and then add Nafion solution. The added amount satisfies: the ratio of the mass of the metal substance to the mass of the metal oxide to the mass of Nafion is 8:2. After the above-mentioned catalyst, conductive substance and dispersion solvent are mixed, ultrasonic dispersion is used to disperse the slurry. The ultrasonic dispersion time is 30 minutes. After the dispersion is completed, the slurry is evenly sprayed on the proton exchange membrane by ultrasonic spraying, and then the obtained membrane electrode is assembled to the electrolyzer for testing. The test results are as follows Figure 8 .
Claims
1. A method for preparing a high-performance membrane electrode anode catalyst layer, It is characterized in that The anode catalyst layer slurry includes a metal oxide catalyst, a metal substance with excellent electrical conductivity, liquid alcohol, an ion polymer, and ultrapure water, and is dispersed in multiple stages to obtain the anode catalyst layer slurry; The method for preparing the membrane electrode anode catalyst layer comprises the following steps: mixing various substances included in the anode catalyst layer slurry, dispersing them in multiple stages, and then uniformly dispersing the catalyst slurry on the proton exchange membrane by spraying or coating.
2. A method for preparing a high-performance membrane electrode anode catalyst layer according to claim 1, It is characterized in that The metal oxide catalyst includes at least one of iridium oxide, ruthenium oxide, and iridium-ruthenium binary oxide.
3. A method for preparing a high-performance membrane electrode anode catalyst layer according to claim 1, It is characterized in that The metal substance with excellent electrical conductivity includes at least one of platinum black, iridium black, ruthenium black, palladium black and cobalt black.
4. A method for preparing a high-performance membrane electrode anode catalyst layer according to claim 1, It is characterized in that The liquid alcohol includes a mixture of one or more of ethanol, n-propanol, isopropanol, n-butanol, ethylene glycol, ethoxyethanol, and methoxyethanol.
5. A method for preparing a high-performance membrane electrode anode catalyst layer according to claim 1, It is characterized in that The liquid alcohol and ultrapure water in the anode catalyst layer slurry are mixed in a volume ratio of 9:1-1:
9.
6. A method for preparing a high-performance membrane electrode anode catalyst layer according to claim 1, It is characterized in that The noble metal loading of the metal oxide catalyst in the anode catalyst layer slurry is 0.01-3 mg / cm 2 .
7. A method for preparing a high-performance membrane electrode anode catalyst layer according to claim 1, It is characterized in that The ratio of the metal substance with excellent electrical conductivity to the metal oxide is 1:1-1:
9.
8. A method for preparing a high-performance membrane electrode anode catalyst layer according to claim 1, It is characterized in that The multi-stage dispersion includes one or more of ball milling dispersion, ultrasonic dispersion and high shear dispersion.
9. A method for preparing a high-performance membrane electrode anode catalyst layer according to claim 1, It is characterized in that The spraying or coating means includes one or more of electrostatic spraying, ultrasonic spraying, scraper coating, roller coating and slit coating.
10. A method for preparing a high-performance membrane electrode anode catalyst layer according to claim 1, It is characterized in that The ionic polymer is a Nafion solution, and the added amount thereof satisfies that the ratio of the mass of the metal substance to the mass of the metal oxide to the mass of the Nafion is 1:1-9:1.
Citation Information
Cited By
Preparation method of anode catalyst slurry of PEM electrolyzed water, slurry and catalytic layer
CN121496445A
